Research Based Learning: Added Value in Students' Science Critical Thinking Skills - Jessy Viny Reyk; Marleny Leasa; Melvie Talakua; John Rafafy Batlolona (Jurnal Penelitian Pendidikan IPA, 2022)
Many new learning models in the 21st century have emerged in improving students' academic skills, one of which is research-based learning (RBL). This pedagogic and constructivist model connects research and learning in improving students' critical thinking skills (CTS). The results of the study show that studies in empowering students' CTS using RBL are still limited. Therefore, exploration and deeper measurement of CTS with the RBL model were carried out through this study. The purpose of this study was to improve students' CTS using the RBL learning model. The results of the ANCOVA test showed that there was an effect of the RBL model in improving students' CTS. Descriptive data also shows that the average value of CTS is 72.70 using RBL, while students who take part in learning using conventional models show an average value of critical thinking skills of 58.30. Thus, RBL can be recommended in increasing the CTS of elementary school students in science learning.